2009
DOI: 10.1007/s10512-009-9155-9
|View full text |Cite
|
Sign up to set email alerts
|

Electron-microscopic investigation of boron carbide irradiated in a fast reactor

Abstract: Since boron carbide is extensively used in building reactors, it is of scientific and practical interest to investigate radiation defects in it.Radiation Defects. A characteristic feature of boron carbide is that neutron capture results in the formation of helium and lithium, which according to investigations form flat pores [1].The experimental samples of boron carbide are pellets fabricated by hot pressing and irradiated in BN-350 at 370°C to boron burnup 2.8% (26·10 26 captures/m 3 ). The increase of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The results we obtained here were coherent with previous ones [10][11][12][13][14][15]. However, implanting helium in a thin slab led to different behaviours as compared to those observed in homogeneously implanted or neutron irradiated materials.…”
Section: Helium Clusters Observationssupporting
confidence: 90%
See 1 more Smart Citation
“…The results we obtained here were coherent with previous ones [10][11][12][13][14][15]. However, implanting helium in a thin slab led to different behaviours as compared to those observed in homogeneously implanted or neutron irradiated materials.…”
Section: Helium Clusters Observationssupporting
confidence: 90%
“…Helium accumulates in flat, high pressure and parallel bubbles (mainly parallel to the (111) planes [10][11][12][13] and also to the (100) and (110) planes [12][13][14][15] of the rhombohedral structure). In fast neutron reactors, the combination of heat release and helium production induces strong radial thermal gradients and extensive cracking of the absorber pellets [4,16,17] as shown in Figure 4.…”
Section: Introductionmentioning
confidence: 99%
“…When boron carbide itself is irradiated with thermal neutrons, lithium and helium ions are produced by neutron capture events of 10 B, which cause bubbles to form in the structure. This does not affect nano-crystallinity 15,16 , although micropores are observed. Amorphisation is possible using H + ion radiation, which alters the structure chemically 17 , but 1MeV electron impacts again do not affect the gross crystal structure 18 ; 2MeV impacts are required to induce amorphisation through impact.…”
Section: Introductionmentioning
confidence: 94%
“…Unfortunately, this also means that the diffusion coefficients obtained from 1550°C are greatly influenced by B 4 C vaporization (and by bubble migration) resulting in data acquired from 1550°C being no longer exploitable (except for the determination of the total amount of implanted He). _ Tarasikov 44 investigated by TEM the evolution of He bubbles in B 4 C after tens of hours of annealings. It was observed that after annealing 60 h at 1400°C, the intragranular bubbles shapes evolved but not their volume suggesting no bubble merging and consequently no bubble diffusion in the material.…”
Section: He Release Curves Modellingmentioning
confidence: 99%